2007
DOI: 10.1016/j.ajog.2007.06.027
|View full text |Cite
|
Sign up to set email alerts
|

Differential expression of microRNAs with progression of gestation and inflammation in the human chorioamniotic membranes

Abstract: Objective-The aim of this study was to identify differential expression of microRNAs (miRNAs) in chorioamniotic membranes with advancing gestation, labor, and inflammation.Study design-Expression profiles of 157 miRNAs in the chorioamniotic membranes were obtained from patients in the following groups: 1) term not in labor (n=10); 2) term in labor (n=10); 3) preterm labor with histologic chorioamnionitis (n=9); and 4) without histologic chorioamnionitis (n=10).Results-More than 95% of the miRNAs screened were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
41
0
1

Year Published

2008
2008
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(44 citation statements)
references
References 35 publications
2
41
0
1
Order By: Relevance
“…Studies have also provided evidence for the potential role of miRNAs in human parturition, as seen by their differential expression patterns in the chorioamnion between preterm and term labor [35] or histologic chorioamnionitis [36]. In this study, miR-320a and miR-18a, had significantly altered expression in AMC after MALP-2 treatment compared to untreated controls (Figure 6B).…”
Section: Discussionsupporting
confidence: 52%
“…Studies have also provided evidence for the potential role of miRNAs in human parturition, as seen by their differential expression patterns in the chorioamnion between preterm and term labor [35] or histologic chorioamnionitis [36]. In this study, miR-320a and miR-18a, had significantly altered expression in AMC after MALP-2 treatment compared to untreated controls (Figure 6B).…”
Section: Discussionsupporting
confidence: 52%
“…Recent studies have also identified a labor-associated increase of hsa-miR-223-3p in human cervical tissue 8 and in chorioamniotic membranes in the presence of inflammation. 9 Hsa-miR-223-3p has been found to target IKKa during monocyte-macrophage differentiation, which suggests a possible role in the noncanonical and canonical NF-kB pathways, 35 which are important in both term and preterm labor.…”
Section: Ajogorgmentioning
confidence: 98%
“…6 A number of recent studies have examined miRNA expression during labor onset in reproductive tissues that have included the placenta, 7 cervix, 8 and fetal membranes. 9 Renthal et al 10 reported that the miR-200 family of miRNAs are upregulated in laboring murine and human myometrium at term. In mouse myometrium, ZEB1 and ZEB2 were identified as 2 targets that act as transcriptional repressors of the contractionassociated genes, which include the oxytocin receptor and connexin-43, through a mechanism that involves the repression of STAT5b, a transcriptional repressor of the P4 metabolizing enzyme 20a-hydroxysteroid dehydrogenase.…”
mentioning
confidence: 98%
“…The daunting numbers of miRs identified at the present time and the multifunctionality of any given miR makes identification of developmentally essential miR activity difficult to discern in such a background. However, a single study found that miR-223 and -338 were dramatically increased in both the mother and the fetus in the context of chorioamnionitis implicating the effects of maternal infection on miR-regulated gene expression (Montenegro et al, 2007).…”
Section: Fetal Programming and Epigeneticsmentioning
confidence: 99%